1999
DOI: 10.2494/photopolymer.12.591
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Acetal-Based BUY Resists

Abstract: Physical and lithographic properties of structurally diverse acetal-derivatized hydroxy styrene polymers are reported. The dissolution and thermal properties of the acetalblocked polymers vary with the size of the pendent acetal moiety. The lithographic performance of the resists containing "bulky" acetal-derivatized polymers was found to be superior to those containing non-bulky acetal functionalized polymers. In the cases where the acidolysis products of the bulky acetal-based polymers are non-volatile alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The synthetic method to incorporate desired acetal protections into PHS-based polymer was written in our previous paper 14,15 Fractionated polymer was prepared with silica gel column chromatography with the mixture of ethylacetate and chloroform as the eluent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic method to incorporate desired acetal protections into PHS-based polymer was written in our previous paper 14,15 Fractionated polymer was prepared with silica gel column chromatography with the mixture of ethylacetate and chloroform as the eluent.…”
Section: Methodsmentioning
confidence: 99%
“…LWR value was basically measured with S-9380 ® CD-SEM with rectangle scan mode where the measurement gate console could cover more than 2000 nm length of the line in one time image scan 14 . Beside, the patterned wafer with MET@ ALS (LBNL) was 4 inch size, so that LWR value was measured by taking top-view images with S-4800 ® (SEM microscope, Hitachi) by 5 times repeating steps in long length direction to cover 2000 nm length.…”
Section: Methodsmentioning
confidence: 99%
“…Reactive polymers with functional groups protected with vinyl ethers have been synthesized and used for various applications, as reported in the literatures [26][27][28][29][30][31]. We found that the polymers containing the iBEA units were readily deprotected under single-stimulus conditions, such as hydrolysis without an acidic catalyst or acidolysis at room temperature under photoirradiation in the presence of PAG [25].…”
mentioning
confidence: 92%
“…[4][5][6] In this study, structural effect of protecting group on KrF and ArF resist was investigated. For a hydroxystyrene resist, we prepared three terpolymers according to the bulkiness and activation energy of protecting group; poly [4-hydoxystyrene-co-t-butoxystyreneco-2-methyl-2-adamantyl methacrylate] as a high activation type polymer, poly [4-hydoxystyrene-co-t-butoxystyrene-co-2-ethyl-2-adamantyl methacrylate] as a mid activation type polymer, and poly [4-hydoxystyrene-co-t-butoxystyrene-co-2-isopropyl-2-adamantyl methacrylate] as a low activation type polymer, respectively.…”
Section: Introductionmentioning
confidence: 99%